Cigarette Smoke Exposure and Stunting Among Under-five Children in Rural and Poor Families in Indonesia - Nurmiati Muchlis; Rezky Aulia Yusuf; Arni Rizqiani Rusydi; Nur Ulmy Mahmud; Nurul Hikmah; Andriany Qanitha; Abdillah Ahsan (SAGE Publishing, 2023)
Cigarette smoke exposure in mothers and children is highly prevalent in Asia, especially among rural and poor families. Second-hand smoke exposure might affect the nutritional status of children. Despite the emerging double burden of malnutrition and the very high prevalence of smoking in Indonesia, few studies have examined the effects of parental smoking on children's nutritional status. This study aims to measure the relationship between family smoking behavior and the occurrence of stunting in children under 5 years. This cross-sectional study used a purposive sampling technique, with 221 households with children aged 0 to 59 months from poor areas in Indonesia. Exposure to cigarette smoke is assessed using The Secondhand Smoke Exposure Scale questionnaire. The outcome measured is child stunting (height-for-age Z -score). The prevalence of stunting was estimated at 145 (65.6%). Children living with smoking parents were counted for 157 (71%), and most smoking exposure comes from fathers 147 (67.4%). The predictors of stunting in children under 5 years were a smoker father with (AOR 1.8; 95% CI 1.281-4.641), both parents are smokers increasing the risk of stunting with (COR 3.591; 95% CI 1.67-3.77), being exposed of smoke for more than 3 hours a day increase the risk of stunted children (COR 2.05; 95% CI 1.214-3.629), and using traditional cigarette or kretek expand the risk of stunting (AOR 3.19; 95% CI 1.139-67.785). The findings demonstrate the negative impact of parental smoking on children's growth, reinforcing the importance of reducing smoking prevalence by imposing a smoke-free home policy in the stunting prevention strategy.